Development and analysis of physical and mathematical models of combustion of single drops of coal-water fuel in furnaces of boiler plants - E. S. Flek (Омский научный вестник)
In the article there is considered one of directions of increase of efficiency of use of coal — burning coal-water fuel (CWF). There is developed a physical and mathematical models of the combustion of droplets of CWF with division of the process into a sequence of repetitive stages of evaporation and burning out of the solid phase. The formula for calculating the time of burnout of a single drop of CWF on the basis of the Sreznevsky equation is obtained. The results of calculation of time of burning of a drop depending on a radius of a drop and a moisture content are presented.